Processing of Al-CuO Composite Powders by High-Pressure Torsion: the Effect of Rotation Number on their Mechanical and Corrosive Properties - Bulutsuz, Asli Gunay; Bruder, Enrico; Dikici, Burak (SPRINGER, 2025)
This study provides a detailed investigation of the manufacturing, mechanical, and corrosion properties of Al-CuO composite materials using a two-stage solid-state synthesis route. The Al and CuO powders were subjected to high-energy ball milling followed by consolidation via high-pressure torsion (HPT) at room temperature. The aim was to generate mechanically robust samples with Al2O3 reinforcing particles through internal oxidation. Microstructural analyses demonstrate that HPT processing of ball milled powders with a single rotation is already sufficient to generate crack-free samples. XRD peak intensities decrease with significant peak shifts in all phases which indicates the partial dissolution of CuO. Furthermore, the number of HPT rotations has a notable impact on the mechanical and corrosion properties of the composites. Increasing the number of rotations from 1 to 10 leads to a 79.82% increase in sample hardness and 35.12% increase in ultimate tensile strength. Simultaneously, the corrosion rate of the composites decreased, paired with an increase in polarization resistance by more than factor of 5. This highlights the potential of severe plastic deformation processing to generate composite materials with an optimal combination of mechanical and corrosion properties.
Keywords: characterisation; composite; corrosion; high-energy ball milling; high-pressure torsion; ALUMINUM-MATRIX COMPOSITES; IN-SITU; MICROSTRUCTURE; CONSOLIDATION; NANOCOMPOSITE; FABRICATION; SYSTEM; Materials Science